2020
DOI: 10.3390/ijms21093080
|View full text |Cite
|
Sign up to set email alerts
|

Sinomenine Inhibits Migration and Invasion of Human Lung Cancer Cell through Downregulating Expression of miR-21 and MMPs

Abstract: Sinomenine is an alkaloid derived from Sinomenium acutum. Recent studies have found that sinomenine can inhibit various cancers by inhibiting the proliferation, migration and invasion of tumors and inducing apoptosis. This study aims to investigate the effect and mechanism of sinomenine on inhibiting the migration and invasion of human lung adenocarcinoma cells in vitro. The results demonstrate that viabilities of A549 and H1299 cells were inhibited by sinomenine in a dose-dependent manner. When treated with s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(19 citation statements)
references
References 57 publications
0
19
0
Order By: Relevance
“…This is a cellular de-differentiation process associated with cancer metastasis, but it is also a normal process during embryonic development and wound healing [92]. Cell adhesion, matrix compounds or cell-microenvironment interaction genes also adapt their expression to the new cellular program and environment [93,94]. Our results show that SA modified the expression of genes related to cell adhesion, the ECM and ECM remodeling, and many of these genes are associated with EMT.…”
Section: Discussionmentioning
confidence: 73%
“…This is a cellular de-differentiation process associated with cancer metastasis, but it is also a normal process during embryonic development and wound healing [92]. Cell adhesion, matrix compounds or cell-microenvironment interaction genes also adapt their expression to the new cellular program and environment [93,94]. Our results show that SA modified the expression of genes related to cell adhesion, the ECM and ECM remodeling, and many of these genes are associated with EMT.…”
Section: Discussionmentioning
confidence: 73%
“…In addition, the antitumor effects of sinomenine have been found in various cancers. Shen et al reported that sinomenine restrained migration and invasion of lung cancer cells by repressing miR-211 and MMPs [24]. Moreover, sinomenine enhanced renal carcinoma cell apoptosis by promoting autophagy and suppressing the PI3K/AKT/mTOR pathway [25].…”
Section: Discussionmentioning
confidence: 99%
“…Increasing evidence demonstrates miRNA-21 involvement in enhancing cancer proliferation and metastasis via inducing molecular pathways such as Akt and matrix metalloproteinases (MMPs). Anti-tumor compounds such as sinomenine reduce miRNA-21 expression in disrupting lung cancer progression [ 230 , 231 ]. By PTEN downregulation, miRNA-21 promotes the expression of Akt and extracellular-signal regulated kinase (ERK) pathways, leading to the gefitinib resistance of lung cancer cells [ 232 ].…”
Section: Microrna and Pten Relationshipmentioning
confidence: 99%